Technology - Business Source Premier (Business Source Premier, 2021)
Here are entered general works on the application of technical knowledge to practical problems, including the development and study of machines, tools, and techniques of manufacturing and production methods and processes. Use only if a narrower term does not apply (e.g., "Educational technology" or "Technocracy"). Works on the technology used in particular wars are entered under the name of the war subdivided by -- Technology, e.g., "World War, 1939-1945 -- Technology." [EPC]
Keywords: Sciences économiques; Thésaurus de base de données